Metal or nonmetal cooperation with a phenyl group: route to catalysis? a computational investigation - Ghatak, Kamalika; Mane, Manoj; Vanka, Kumar (ACS Catalysis, 2013)
Full quantum mechanical calculations demonstrate that cooperativity in the form of the activation of the M-C bond (M: transition metal or boron, C: the ipso carbon of the coordinated phenyl group) can lead to effective catalysis pathways. Calculations show that the presence of an aromatic bidentate ligand attached to a transition metal, or even a main group element, such as boron, can lead to effective catalysts for,a, range of important reactions, such as the dehydrogenation of ammonia borane and formic acid and the activation of the N-H, bond in aromatic amities. Moreover, it is shown that the design of tridentate pincer complexes with the aromatic group at a terminal end can lead to effective M-C cooperativity. As such, the current work introduces a new concept in cooperativity and bond activation chemistry.
Keywords: catalysis; Density functional theory; metal-ligand cooperativity; small molecule activation

Synthesis of alpha,beta-unsaturated delta-lactones by vinyl acetate mediated asymmetric cross-aldol reaction of acetaldehyde: mechanistic insights - Kumar, Manjeet; Kumar, Arvind; Rizvi, Masood; Mane, Manoj; Vanka, Kumar; Taneja, Subhash C.; Shah, Bhahwal Ali (European Journal of Organic Chemistry, 2014)
A tandem asymmetric cross-aldol reaction involving the in situ generation of acetaldehyde from vinyl acetate has been developed that may resolve the challenges associated with the handling of acetaldehyde. The simple protocol, mild reaction conditions and unique harmony of an organocatalyst with a biocatalyst make this method a valuable tool for the synthesis of asymmetric beta-hydroxy aldehydes. By using this methodology we have accessed alpha,beta-unstaurated delta-lactones as well as isochromenones with high enantioselectivities from both asymmetric beta-hydroxy aldehydes and ketones. Systemic density functional theory (DFT) studies were also performed to gain mechanistic insights into the role of hydrogen bonding in the asymmetric cross-aldol reaction of acetaldehyde and in the key cis/trans isomerisation step in the synthesis of d-lactones.
Keywords: Aldol reactions; asymmetric catalysis; lactones; reaction mechanisms

Computational survey of ligand properties on iron(III)-iron(II) redox potential: exploring natural attenuation of nitroaromatic compounds - Rizvi, Masood Ahmad; Mane, Manoj; Khuroo, Mohammad Akbar; Peerzada, Ghulam Mustafa (Monatshefte Fur Chemie, 2017)
This study is a computational investigation of the ligand effect on the redox potential of iron redox couple aimed at screening these systems for novel applications. The influence of common and naturally available organic compounds with diverse ligand characteristics (nature of donor site, chelation, pre-organization, degree of back acceptance) on the redox potential of iron(III)-iron(II) redox couple has been theoretically calculated using an appropriate level of density functional theory (DFT). The DFT calculated redox potentials of iron complexes are explored to supplement, corroborate, and predict the experimental behavior of the studied systems towards environmental reduction of nitroaromatic compounds to corresponding anilines. The comparative avidity of iron complexes with cysteine derivatives for the reduction of nitroaromatic compounds has been theoretically explored and based on structure-activity relationship; new iron complexes with a range of reactivity and enhanced ability towards nitroaromatic reduction have been predicted.
Keywords: Catechol derivatives; computational chemistry; Density functional theory; Iron complexes; Ligand effect on redox potential; Natural attenuation; Nitroaromatic compounds

Secondary interactions arrest the hemiaminal intermediate to invert the modus operandi of schiff base reaction: a route to benzoxazinones - Patel, Ketan; Deshmukh, Satej S.; Bodkhe, Dnyaneshwar; Mane, Manoj; Vanka, Kumar; Shinde, Dinesh; Rajamohanan, Pattuparambil R.; Nandi, Shyamapada; Vaidhyanathan, Ramanathan; Chikkali, Samir H. (Journal of Organic Chemistry, 2017)
Discovered by Hugo Schiff, condensation between amine and aldehyde represents one of the most ubiquitous reactions in chemistry. This classical reaction is widely used to manufacture pharmaceuticals and fine chemicals. However, the rapid and reversible formation of Schiff base prohibits formation of alternative products, of which benzoxazinones are an important class. Therefore, manipulating the reactivity of two partners to invert the course of this reaction is an elusive target. Presented here is a synthetic strategy that regulates the sequence of Schiff base reaction via weak secondary interactions. Guided by the computational models, reaction between 2,3,4,5,6-pentafluoro-benzaldehyde with 2-amino-6methylbenzoic acid revealed quantitative (99%) formation of 5-methyl-2-(perfluoropheny01,2-dihydro-4H-benzo[d][1,3]oxazin-4-one (15). Electron donating and electron withdrawing ortho-substituents on 2-aminobenzoic acid resulted in the production of benzoxazinones 936. The mode of action was tracked using low temperature NMR, IN vis spectroscopy, and isotopic (O-18) labeling experiments. These spectroscopic mechanistic investigations revealed that the hemiaminal intermediate is arrested by the hydrogen-bonding motif to yield benzoxazinone. Thus, the mechanistic investigations and DFT calculations categorically rule out the possibility of in situ imine formation followed by ring-closing, but support instead hydrogen-bond assisted ring-closing to prodrugs. This unprecedented reaction represents an interesting and competitive alternative to metal catalyzed and classical methods of preparing benzoxazinone.

Polymer nanorings with uranium specific clefts for selective recovery of uranium from acidic effluents via reductive adsorption - Kushwaha, Shilpi; Mane, Manoj; Ravindranathan, Sapna; Das, Amitava (ACS Sensors, 2020)
Nanostructured polymeric materials, functionalized with an appropriate receptor, have opened up newer possibilities for designing a reagent that shows analyte-specific recognition and efficient scavenging of an analyte that has either a detrimental influence on human physiology and environment or on its recovery for further value addition. Higher active surface area, morphological diversity, synthetic tunability for desired surface functionalization, and the ease of regeneration of a nanostructured material for further use have provided such materials with a distinct edge over conventional reagents. The use of a biodegradable polymeric backbone has an added significance owing to the recent concern over the impact of polymers on the environment. Functionalization of biodegradable sodium alginate with AENA (6.85% grafting) as the receptor functionality led to a unique open framework nanoring (NNRG) morphology with a favorable spatial orientation for specific recognition and efficient binding to uranyl ions (U) in an aqueous medium over a varied pH range. Nanoring morphology was confirmed by transmission electron microscopy and atomic force microscopy images. The nanoscale design maximizes the surface area for the molecular scavenger. A combination of all these features along with the reversible binding phenomenon has made NNRG a superior reagent for specific, efficient uptake of UO22+ species from an acidic (pH 3-4) solution and compares better than all existing UO22+-scavengers reported till date. This could be utilized for the recovery of uranyl species from a synthetic acidic effluent of the nuclear power. The results of the U uptake experiments reveal a maximum adsorption capacity of 268 mg of U per g of NNRG in a synthetic nuclear effluent. X-ray photoelectron spectroscopy studies revealed a reductive complexation process and stabilization of U(IV)-species in adsorbed uranium species (U@NNRG).
Keywords: biodegradable polymeric backbone; molecular recognition; nanostructured material; sodium alginate; uranium; uranyl-specific receptor